Geneticization from the Point of View of Geneticists: Practices, and Prospectsof Personalized and Predictive Molecular Genetic Testing in Russia - Vitaliy Lekhtsier; Julia Shekunova (Journal of Economic Sociology, 2022)
The article offers the results of a qualitative empirical sociological analysis of medical geneticists on their assessment of the problems, opportunities, and prospects of predictive genetic testing in Russia as a relatively new branch of healthcare. The gradual introduction of a new genetic biopredictive technology into everyday life is regarded in the article as a phenomenon of geneticization or genomization. The analysis takes into account three main categories of medical geneticists: physician geneticists (who deal with patients), laboratory geneticists, and academic geneticists working in medical universities. The analysis revealed, firstly, those positions within the professional community of medical geneticists that can be called consensual. For example, concerning the problematic nature of the methodology for calculating risks associated with the development of multifactorial diseases, or with regard to the high cost of testing now and its inevitable reduction with biotechnological progress; about the reluctance of people in Russia to take preventive care of their health, and about the special prospects and demand for the oncology and pharmacogenetics industries. Other points of consensus include the clinical benefit of the results of predisposition testing for multifactorial diseases, the prospects for the development of the industry as a whole, etc. Between the poles of consensus and dissensus lie different views of professionals on the possibilities and prospects of predictive genetic testing practices. The results of the empirical research presented in the article are grounded in a historical and theoretical review of the scientific literature on the problem of the article. Initial conclusions are drawn as part of the study of social science (mostly Western) geneticization and its social consequences. The relevance of the conducted research is especially evident in the background of a large deficit of empirical studies of geneticization practices in Russia.